Como ocorrem os movimentos da mandíbula e da cabeça em sujeitos com disfunção temporomandibular e em sujeitos saudáveis? - Grüninger, Bruno Leonardo da Silva (2017)
Considering the lack of studies assessing the relationship between temporomandibular joint and neck components in a dynamic approach, this study aimed to investigate kinematics and motor control of the head and jaw in functional and isolated activities, and to evaluate cervical muscle performance and motor control of the head in temporomandibular disorder (TMD) patients compared to healthy subjects. Kinematics of head and jaw were recorded from 71 women (Healthy Group – HG: N= 33; Temporomandibular Disorder Group – TMDG: N=38) during neck movements (flexion-extension, rotation and lateral bending), and functional tasks (maximal mouth opening (MMO), speaking, chewing and computer use). Median frequency was calculated for head positions in functional tasks. Cross-correlation analysis was performed for the time series of jaw and head recorded in functional tasks. Motor control of the head (joint position sense - JPS), and cervical muscle performance (craniocervical flexion test - CCFT) were also tested. TMDG and HG were compared using independent t-test or Mann-Whitney test. No difference was observed in CCFT and JPS, while jaw depression was larger in HG. Median frequency was higher for head position of HG in sagittal plane during computer use in relation to TMDG. It may indicate more variation and better motor strategies in HG. Cross-correlation analysis showed a clear negative correlation between head and jaw in MMO. However, the consistency of this correlation was weak in other tasks. It seems that the higher the biomechanical requirement the stronger the correlation. Further studies should focus on more complex tasks.